Buddhism and worldliness in modern Taiwan - Qurtuby, Sumanto Al (Journal of contemporary religion, 2020)
Buddhism has long been typified as an ascetic religion that puts emphasis on spirituality and otherworldliness. This article, examining the linkage between Buddhism and worldliness in contemporary Taiwan, challenges this conventional dominant view. Contrary to popular opinion, Taiwan has witnessed the emergence of the ‘earthly Buddha’, characterized by the desire to engage with worldly matters such as altruistic, capitalist, and economic activities. Challenging Weber’s classical and controversial thesis and argument, this article shows that the Buddhist religious tradition, as practiced by such Buddhist groups as Fo Guang Shan, Tzu Chi Foundation, and Dharma Drum Mountain, has fostered the same Geist (spirit) as Protestantism and thereby contributed to the rise of bourgeois rational capitalism and anything related to worldly affairs, including the economy, charity, and humanity in contemporary Taiwan.